2010
DOI: 10.1158/0008-5472.can-10-1675
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of miR-196s to HOXC8 Messenger RNA Correlates with Breast Cancer Cell Migration and Metastasis

Abstract: Expression profiling has identified metastasis-associated microRNAs (miRNA) but technical limitations hinder the discovery of metastasis-suppressing miRNAs. In this study, we sought metastasis-suppressing miRNAs by functional screening. Individual miRNAs were lentivirally introduced into metastatic MDA-MB-231 breast cancer cells and analyzed for effects on cell migration, a critical step in cancer metastasis. Among 486 miRNAs screened, 14 were identified that included all of the members of the miRNA-196 family… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(152 citation statements)
references
References 28 publications
10
139
1
2
Order By: Relevance
“…39 Moreover, enforced expression of miR-196a reduced in vitro invasion and in vivo spontaneous metastasis of breast cancer cells. 40 In addition, overexpression of miR-196a inhibited the proliferation of human adipose tissue-derived mesenchymal stem cells while enhancing osteogenic differentiation. 41 Our results show that NPC cells become radioresistant by reducing the expression of miR--196a, and expression of miR-196a restores the sensitivity of radioresistant NPC to radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…39 Moreover, enforced expression of miR-196a reduced in vitro invasion and in vivo spontaneous metastasis of breast cancer cells. 40 In addition, overexpression of miR-196a inhibited the proliferation of human adipose tissue-derived mesenchymal stem cells while enhancing osteogenic differentiation. 41 Our results show that NPC cells become radioresistant by reducing the expression of miR--196a, and expression of miR-196a restores the sensitivity of radioresistant NPC to radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its expression was observed to be associated with the tumor prognosis in certain patients (20)(21)(22). It has been determined that miR-337 is a key regulator of certain oncogenes, including homeobox C8 gene and transforming growth factor-β receptor type II (23,24). Previous studies have demonstrated significantly reduced expression levels of miR-337 in pancreatic ductal adenocarcinoma tissue samples when compared with adjacent nonmalignant tissues (25).…”
Section: Discussionmentioning
confidence: 99%
“…miR-196a downregulation can lead to HOX-B7 and BMP-4 overexpression, which may be responsible for the early steps of melanoma development (Braig et al, 2010). Li et al (2010) showed that overexpression of miR-196a or miR-196b inhibited the invasion and metastatic capacity of breast cancer cells both in vitro and in vivo, suggesting miR-196a may play a role in tumor suppression in breast cancer. This contradictory role of miR-196a in regulating cancer development is poorly understood.…”
Section: Discussionmentioning
confidence: 99%